The Effect of Steaming and Length of Storage on Physical Characteristics of Turtle Dove Feed - . Yatno; S. Purwanti (Jurnal Ilmu dan Teknologi Peternakan, 2010)
The purpose of research was to investigate the influence of steamed preconditioning the pellet on water content, water activity (Aw), physical appearance and pellet fineness. The experiment was carried out in 2 x 3 factorial arrangement according to completely randomized design with 3 replications for each treatment combination. The factor A is the pellet-making process (steam/MBS and non steam/MBNS), while factor B is the length of storage (0, 2 and 4 weeks). The parameters observed were water content, water activity, physical appearance and pellet fineness. Data were  analyzed by  STASTS program version  2.6  and followed by Multiple Range Test if the treatments were significant. The results showed that  treatment with MBS or MBNS and the length of storage did not affect physical appearance (colour, smell and taste) of the pellet. MBS treatment significantly reduced water contents of pellet compared with MBNS treatment (12.04 vs 11.45%) and significantly increased water activity (0.75 vs 0.80). The length of storage (0, 2 and 4 weeks) increased water content of pellet, i.e. 10.84, 12.02 and 12.47%, respectively. In conclusion, steamed preconditioning treatment (MBS) reduced water content and increased water activity of pellet, while  the length of storage significantly increased water content and water activity but reduced pellet fineness.